Effects of dose rate absorption in extracellular potassium concentration of red cells concentrates. (February 2020) - Mori, A.B.; Kappke, J.; Lima, T.A.; Antoniassi, M.; Ribeiro, A.M.T.; Goulart, R.; Galerani, A.P.; Cardoso, G.; Conceição, A.L.C.
Abstract: Blood irradiation is an essential practice to prevent transfusion-associated graft versus host disease (TA-GVHD), a rare and fatal syndrome. In this procedure, the T lymphocytes are inactivated; otherwise, after transfused to immunodepressed patients, they can trigger the TA-GVHD in the blood receptor. The irradiation procedure can be performed either by a specific irradiator or by devices used for the treatment of cancer patients, such as the linear accelerator. This study aimed to deliver a total dose of 25 Gy in blood bags at different dose rates using a blood specific irradiator and a linear accelerator in order to monitor the extracellular potassium concentration as a function of the dose rate for 28 days, which is the expiration time of the irradiated bag. Blood was collected from 10 volunteers of the Biobank of Clinics Hospital of Federal University of Parana, Brazil. The volume of each concentrated blood bag was divided into three parts: one for inspection sample and the other two irradiated at different dose rates (135 cGy/min, 456 cGy/min, 545 cGy/min - linear accelerator and 448 cGy/min - Gammacell 1000 with cesium-137). For each dose rate, the extracellular potassium concentration was determined (by ion-specific electrode (ISE) indirect method) immediately after irradiation (day 1) and every seven days (day 7, 14, 21 and 28), resulting in 150 values of K-concentration. The extracellular potassium concentration has increased during the first seven days of the irradiation, then started to point downward, tending to the control value after 28 days, suggesting the action of the cell repair mechanisms. Additionally, a correlation between increased extracellular potassium concentration and increased dose rate was also observed.